2020
DOI: 10.1128/msphere.00715-20
|View full text |Cite
|
Sign up to set email alerts
|

Tn-Seq Analysis Identifies Genes Important for Yersinia pestis Adherence during Primary Pneumonic Plague

Abstract: Following inhalation, Yersinia pestis rapidly colonizes the lung to establish infection during primary pneumonic plague. Although several adhesins have been identified in Yersinia spp., the factors mediating early Y. pestis adherence in the lung remain unknown. To identify genes important for Y. pestis adherence during primary pneumonic plague, we used transposon insertion sequencing (Tn-seq). Wild-type and capsule mutant (Δcaf1) Y. pestis transposon mutant libraries were serially passaged in vivo to enrich fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…New analyses, such as gene ranking using TPM counts for each RNA-Seq experiments, will also be implemented. Ultimately, mutant phenotypes associated with specific gene locus could also be added based on signature-tagged mutagenesis screening ( 70 75 ), high-throughput transposon site hybridization procedure ( 76 ), or more recent next-generation sequencing using techniques such as transposon-insertion sequencing or transposon-directed insertion sequencing ( 77 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…New analyses, such as gene ranking using TPM counts for each RNA-Seq experiments, will also be implemented. Ultimately, mutant phenotypes associated with specific gene locus could also be added based on signature-tagged mutagenesis screening ( 70 75 ), high-throughput transposon site hybridization procedure ( 76 ), or more recent next-generation sequencing using techniques such as transposon-insertion sequencing or transposon-directed insertion sequencing ( 77 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TraDIS- Xpress data predicted that expression of maoP was detrimental to the fitness of biofilms grown for 24 h, but a Δ maoP mutation strain biofilm had reduced biofilm biomass and reduced curli biosynthesis compared to the wild-type. A homologue to maoP in Yersinia pestis was identified as having a role in adhesion and may positively regulate adhesin expression [ 60 ]. It is unclear why the defined mutants made less biofilm that the wild-type when TraDIS- Xpress predicted expression of maoP was detrimental to biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that expression of maoP was detrimental to the fitness of biofilms grown for 24 hours, and a Δ maoP mutant biofilm had reduced biofilm biomass and reduced curli biosynthesis compared to the wild type. A homolog to maoP in Yersinia pestis was identified as having a role in adhesion and may positively regulate adhesin expression 61 . Chromosomal organisation of the Ori macrodomain requires both maoP and maoS 36 , however no signal is seen in our data for maoS .…”
Section: Discussionmentioning
confidence: 99%